composition for temporary fixation

KR103036938B1Active Publication Date: 2026-10-21DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020247027742
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-24
Filing Date
2023-01-25
Publication Date
2026-10-21
Estimated Expiration
2043-01-25

Smart Images

  • Figure 112024090201473-PCT00001
    Figure 112024090201473-PCT00001
  • Figure 112024090201473-PCT00002
    Figure 112024090201473-PCT00002
  • Figure 112024090201473-PCT00003
    Figure 112024090201473-PCT00003
Patent Text Reader

Abstract

A composition for temporary fixation characterized by containing the following (A) to (B) and having a storage modulus of 0.66 GPa or less at 23°C. (A) Difunctional (meth)acrylate with a cyclic backbone (B) Photoradical polymerization initiator The above-mentioned cured body is formed by inserting the above-mentioned temporary fixation composition into a PET film, expanding it to a thickness of 50 μm, and curing it under conditions of an integrated light intensity of 5000 mJ / cm2 using a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm2).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a composition used for temporary fixation. Background Technology

[0002] In the manufacture of electronic devices, inorganic materials, such as silicon, are used as substrates. Wafer-type substrates with a thickness of several hundred micrometers, obtained by performing processing on their surfaces such as forming insulating films, circuits, and thinning through grinding, are frequently used. However, since many substrates are made of soft and brittle materials, measures to prevent damage are required, particularly during thinning by grinding. Conventionally, this measure involves attaching a temporary protective tape that can be peeled off after the processing is completed to the side opposite the surface to be ground (also called the back side). While this tape utilizes an organic resin film as its base material and offers flexibility, its strength and heat resistance are insufficient, making it unsuitable for use in high-temperature processes.

[0003] Therefore, a system is proposed that provides sufficient durability against the conditions of back-side grinding or back-side electrode formation processes by bonding a substrate for electronic devices to a support such as silicon or glass with an adhesive in between. At this time, the adhesive layer used to bond the substrate to the support is important. This requires sufficient durability to withstand subsequent processes by bonding the substrate to the support without gaps, and finally, it is necessary to be able to easily peel the thinned wafer from the support, that is, to be temporarily fixed.

[0004] The processing of these wafers primarily involves spin coating, vacuum bonding and photocuring, thinning by grinding and polishing, high-temperature treatment, laser peeling, and removal of temporary fixatives.

[0005] In the spin coating process, in order to uniformly form a film of the prefixing agent on the wafer, it is required that the prefixing agent have a suitable viscosity and be a Newtonian fluid (or have shear viscosity independent of the shear rate).

[0006] In vacuum bonding / UV curing processes, the fixative is required to enable curing by light irradiation, such as ultraviolet (UV) rays, on a support such as glass in a short time, and to have low outgassing (low outgassing).

[0007] In the thinning process involving grinding and polishing, the temporary fixative is required to possess an appropriate hardness capable of maintaining flatness by distributing the load in-plane to prevent localized subsidence of the substrate and avoiding damage caused by the grinding machine's load being applied locally to the substrate. Furthermore, in addition to this, adhesion to the support, an appropriate elastic modulus to protect the edges, and chemical resistance are also required.

[0008] In high-temperature processing, heat resistance is required for the fixative to withstand high-temperature treatment for a long time in a vacuum (e.g., at 300°C or higher for 1 hour or more).

[0009] In the laser peeling process, the fixative is required to be capable of high-speed peeling using a laser such as a UV laser.

[0010] In the removal process, in addition to ease of peeling that allows the substrate to be easily detached from the support, cohesive properties and ease of cleaning are required to ensure that no adhesive residue remains on the substrate after peeling.

[0011] With this background in mind, for example, Patent Document 1 discloses a composition for temporary fixation comprising (A-1) a monofunctional (meth)acrylate in which the Tg of the homopolymer in an alkyl group having 18 or more carbon atoms in the side chain is -100°C to 60°C, (A-2) a polyfunctional (meth)acrylate, (B) a polyisobutene homopolymer and / or a polyisobutene copolymer, and (C) a photoradical polymerization initiator, and is emphasized to have excellent heat resistance, low outgassing, and peelability. Prior art literature

[0012] Patent Document 1: International Publication No. 2021 / 235406 The problem to be solved

[0013] As the demand for more highly integrated and miniaturized electronic devices increases, substrates are being further thinned, and substrates with thicknesses of 70 μm and 50 μm are being commercialized. With such thin substrates, there is a problem in that if the tape on the substrate cracks when peeling off the tape, the electronic device is inevitably damaged by the impact. There is a desire for advancements from conventional technology to further improve tape peelability while satisfying the aforementioned demand, particularly heat resistance. means of solving the problem

[0014] That is, the present invention may provide the following forms.

[0015] Form 1.

[0016] A composition for temporary fixation characterized by containing the following (A) to (B) and having a storage modulus of 0.66 GPa or less of the cured body at 23°C.

[0017] (A) Difunctional (meth)acrylate with a cyclic backbone

[0018] (B) Photoradical polymerization initiator

[0019] The above-mentioned cured body is formed by embedding the above-mentioned temporary fixation composition into a PET film and expanding it until it reaches a thickness of 50 μm, and using a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²)2 Using ) accumulated luminous energy 5000mJ / cm 2 It hardened under the conditions of.

[0020] Form 2.

[0021] (A) component

[0022] (A-1) Aromatic difunctional (meth)acrylate, and

[0023] (A-2) Alicyclic difunctional (meth)acrylate

[0024] A composition for temporary fixation described in Form 1, characterized by including

[0025] Form 3.

[0026] A composition for temporary fixation described in Form 1 or 2 further comprising (C) below.

[0027] (C) Acyclic aliphatic difunctional (meth)acrylate

[0028] Form 4.

[0029] (C) A composition for temporary fixation as described in Form 3, wherein the component comprises an oligomer and / or polymer.

[0030] Form 5.

[0031] A composition for temporary fixation described in Form 3 or 4, wherein the amount of component (A) is 50% or more in the mass ratio of component (A) and component (C).

[0032] Form 6.

[0033] A composition for temporary fixation described in any one of forms 1 to 5, further containing (D) below.

[0034] (D) UV absorber

[0035] Form 7.

[0036] A composition for temporary fixation described in any one of forms 1 to 6, further containing (E) below.

[0037] (E) Monofunctional (meth)acrylate

[0038] Form 8.

[0039] A composition for temporary fixation described in Form 7, containing more than 0% and less than or equal to 50% of component (E) in the mass ratio of component (A) and component (E).

[0040] Form 9.

[0041] A composition for temporary fixation described in any one of Forms 1 to 6, which does not contain monofunctional (meth)acrylate.

[0042] Form 10.

[0043] A composition for temporary fixation described in any one of forms 1 to 9, further containing (F) below.

[0044] (F) Polyfunctional (meth)acrylates with three or more functions

[0045] Form 11.

[0046] A composition for temporary fixation described in Form 10, containing more than 0% and less than or equal to 50% of component (F) in the mass ratio of component (A) and component (F).

[0047] Form 12.

[0048] A cured body of a temporary fixation composition described in any one of forms 1 to 11.

[0049] Form 13.

[0050] A hardened body described in Form 12, having a 2% mass loss temperature of 300°C or higher under a nitrogen atmosphere. Effects of the invention

[0051] According to the present invention, a novel temporary fixing composition can be obtained that exhibits excellent heat resistance for temporary fixing applications and can also suppress tape cracking when the tape is peeled off. Specific details for implementing the invention

[0052] Unless otherwise specifically stated in this specification, numerical ranges are defined to include their upper and lower limits. In this specification, monofunctional (meth)acrylate refers to a compound having one (meth)acryloyl group in one molecule. Polyfunctional (meth)acrylate refers to a compound having two or more (meth)acryloyl groups in one molecule. n-functional (meth)acrylate refers to a compound having n (meth)acryloyl groups in one molecule. As polymerizable functional groups in polyfunctional (meth)acrylates, they may have only acryloyl, only methacryloyl, or both acryloyl and methacryloyl groups.

[0053] In an embodiment of the present invention, a pre-fixation composition (also referred to as a "pre-fixation agent") may be provided, comprising (A) a difunctional (meth)acrylate having a cyclic backbone and (B) a photoradical polymerization initiator, and having a storage modulus of 0.66 GPa or less at 23°C. Furthermore, in this specification, the cured body used for measuring the storage modulus is formed by embedding the pre-fixation composition into a PET film, expanding it until it reaches a thickness of 50 μm, and applying a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²). 2 Using ) accumulated luminous energy 5000mJ / cm 2 It is considered to have hardened under the conditions of.

[0054] The difunctional (meth)acrylate having a cyclic backbone, which is component (A) included in the present composition, plays a role in constituting a rigid backbone within the present composition and can provide the effect of appropriately improving viscosity. Examples of difunctional (meth)acrylates include (A-1) aromatic difunctional (meth)acrylate and (A-2) alicyclic difunctional (meth)acrylate. In a preferred embodiment, component (A) may include either component (A-1) or component (A-2), or may include both components (A-1) and (A-2). It is preferable that component (A) be a monomer.

[0055] (A-1) The aromatic difunctional (meth)acrylate component is generally preferred because it can form a more rigid backbone. More preferably, the rigidity may be further increased by having a condensed ring backbone for the (A-1) component.

[0056] (A-1) An example of a component is 9,9-bis[4-(2-hydroxy C 1 ~ C 20 Alkoxy)phenyl]fluoredi(meth)acrylate, C 1 ~ C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C 1 ~ C 20 Examples include alkyl benzene, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, or structural isomers thereof. Preferably, it may contain a di(meth)acrylate having a condensed ring backbone, for example, a backbone of fluorene, indene, indicene, anthracene, azulene, or triphenylene. One or a combination of two or more of these may be used as component (A-1).

[0057] The alicyclic difunctional (meth)acrylate component (A-2) is a component that can provide a rigid framework that is generally lower than that of the above-mentioned (A-1) component, but generally more rigid than that of acyclic molecules (such as acyclic difunctional (meth)acrylates). In a preferred embodiment, by combining component (A-2) with component (A-1), it is possible to form a cross-linked structure that imparts desirable physical properties to the fixative agent. Preferably, the rigidity may be further increased by having component (A-2) with a condensed ring framework. Preferably, component (A) may include component (A-2) having a condensed ring framework together with component (A-1) having a condensed ring framework. In any embodiment, the number of rings (including condensed rings) possessed by component (A-1) or component (A-2) or both thereof may be at least two, and preferably at least two and no more than five.

[0058] (A-2) An example of a component is C1 ~ C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, 1,3-di(meth)acryloyloxyadamantan, tricyclo-C 10 ~ C 20 Alkanedimethanol di(meth)acrylate (e.g., tricyclodecanedimethanol di(meth)acrylate, etc.), dicycloC 5 ~ C 20 Examples include di(meth)acrylates or their structural isomers. Among alicyclic difunctional (meth)acrylates, alicyclic difunctional (meth)acrylates having an alicyclic backbone with 5 or more carbon atoms are more preferred. As for alicyclic difunctional (meth)acrylates having an alicyclic backbone with 5 or more carbon atoms, one or more selected from tricyclodecanedimethanol di(meth)acrylate and 1,3-di(meth)acryloyloxyadamantan are preferred.

[0059] In an embodiment in which component (A) includes both component (A-1) and component (A-2), the mass ratio of component (A-1) and component (A-2) may preferably be in the range of 1:1 to 4:1, more preferably in the range of 2:1 to 4:1.

[0060] The photoradical polymerization initiator, which is component (B) included in the present composition, is a substance capable of initiating radical polymerization of component (A) (and other monomers included as necessary) upon receiving light irradiation, and refers to a compound whose molecule is cleaved into two or more radicals by irradiation with ultraviolet or visible light (e.g., wavelength 350 nm to 700 nm, preferably 365 nm to 500 nm, more preferably 385 nm to 450 nm). Examples of photoradical polymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(η 5Examples include -2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholine-4-ylphenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholine-4-ylphenyl)-butan-1-one, 1-[4-(phenylthio)phenyl]-1,2-octanedion-2-O-benzoyloxime, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(O-acetyloxime). (B) The component may include one or more of these or a combination of two or more.

[0061] Preferably, component (B) may include an acylphosphine oxide-based compound. Preferred acylphosphine oxide-based compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. As a photoradical polymerization initiator, it is desirable that it is highly sensitive, has excellent deep curing properties due to photofading, and that the absorption wavelength range for generating radicals extends to a relatively long wavelength range. In the preferred compound described above, the absorption wavelength range is up to a wavelength of approximately 440 nm, which is significantly different from the absorption wavelength range of the UV absorber used in the UV laser peeling process described later. That is, the degree of inhibition of UV curing by the UV absorber is small, allowing radical polymerization to be initiated with longer wavelength light. Therefore, the effect of efficiently initiating radical polymerization at a relatively high speed and curing can be obtained even in the presence of a UV absorber.

[0062] In a preferred embodiment, a photoradical polymerization initiator can be selected from absorbance. Specifically, a photoradical polymerization initiator can be selected from one or more compounds that satisfy at least one of the following conditions when dissolved at a concentration of 0.1 mass% in a solvent (e.g., acetanitrile or toluene, etc.) that has no maximum absorption in the wavelength range of 300 nm to 500 nm: that has an absorbance of 0.5 or more at a wavelength of 365 nm, that has an absorbance of 0.5 or more at a wavelength of 385 nm, and that has an absorbance of 0.5 or more at a wavelength of 405 nm. Examples of compounds satisfying such conditions include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(O-acetyloxime) which has an absorbance of 0.5 or higher at a wavelength of 365 nm when dissolved at a concentration of 0.1 mass% with respect to acetanitrile as a solvent, 1-[4-(phenylthio)phenyl]-1,2-octanedion-2-O-benzoyloxime which has an absorbance of 0.5 or higher at wavelengths of 365 nm and 385 nm, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide which have an absorbance of 0.5 or higher at wavelengths of 365 nm, 385 nm, and 405 nm.

[0063] Furthermore, from the perspective of achieving compatibility between curability by a photoradical polymerization initiator and UV laser peeling, bis(η) having an absorption wavelength range of 400 to 500 nm 5 -2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl)titanium can also be used as a photoradical polymerization initiator.

[0064] (B) As a photoradical polymerization initiator, it is preferable to use one or more selected from acylphosphine oxide compounds, titanocene compounds, or α-aminoalkylphenone compounds, in that they have reaction speed, heat resistance after curing, low outgassing properties, and absorption characteristics in a region different from the wavelength of the UV laser used for UV laser peeling described later and also different from the absorption wavelength range of the UV absorber used for UV laser peeling. In addition, as a photoradical polymerization initiator for a resin composition for preventing damage from bonding with a support substrate to a processing substrate to a heating process, rather than a layer for the UV laser peeling process in a composition for temporary fixation having a structure described later, oxime ester compounds may be selected in addition to the above.

[0065] Examples of acylphosphine oxide-based compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.

[0066] As a titanocene compound, bis(η 5 Examples include -2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl)titanium.

[0067] Examples of α-aminoalkylphenone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholine-4-ylphenyl)-butan-1-one.

[0068] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedion-2-O-benzoyloxime and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(O-acetyloxime). Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(O-acetyloxime) is preferred.

[0069] (B) The amount of photoradical polymerization initiator used is preferably 0.01 to 5 parts by mass per 100 parts by mass of component (A) in terms of reaction rate, heat resistance after curing, and low outgassing properties, and is more preferably 0.1 to 1 part by mass. If component (B) is 0.01 parts by mass or more, sufficient curability can be obtained, and if it is 5 parts by mass or less, the effect of low outgassing properties and heat resistance being difficult to impair can be obtained.

[0070] The storage modulus (E') of the cured body of the present composition is 0.66 GPa or less at 23°C. If the storage modulus exceeds 0.66 GPa, a problem arises where the tape easily cracks when a tape peeling process is performed for temporary fixing applications during the manufacture of electronic devices. The storage modulus can be measured using a known viscoelasticity meter, for example, by the method described in the examples described below. The storage modulus (E') of the cured body of the present composition at 23°C is preferably 0.01 GPa or more and 0.66 GPa or less, 0.02 GPa or more and 0.66 GPa or less, or 0.05 GPa or more and 0.66 GPa or less. In a more preferred embodiment, the storage modulus (E') of the cured body of the present composition at 23°C may be 0.01 GPa or more and 0.60 GPa or less, or 0.01 GPa or more and 0.55 GPa or less.

[0071] In addition, from the perspective of ease of laser peeling, it is desirable that the storage modulus (E') of the present composition be 0.01 GPa or higher at 23°C.

[0072] The present composition may include an acyclic aliphatic difunctional (meth)acrylate as component (C). The (C) component can impart flexibility to the cross-linked structure.

[0073] (C) Examples of components include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, and ethylene oxide isocyanurate Examples include modified di(meth)acrylate, caprolactone-modified neopentyl glycol di(meth)acrylate, etc.

[0074] Component (C) may include a monomer, an oligomer or polymer composed of the monomer, or any one of the same. In some embodiments, component (C) may not include a polymer.

[0075] In the case where the composition includes component (C), the amount of component (A) in the mass ratio of component (A) to component (C) may be 50 mass% or more and 95 mass% or less, preferably 50 mass% or more and 90 mass% or less, and more preferably 50 mass% or more and 85 mass% or less. In one embodiment, in the mass ratio of component (A) to component (C), component (A) is 50 mass% or more and 95 mass% or less, and it is also preferable that component (C) does not include a polymer.

[0076] The present composition may include a UV absorber as component (D). A UV absorber refers to a compound whose molecules are cleaved and decomposed or vaporized by irradiation with, for example, ultraviolet or visible light laser, and which causes the loss of adhesion between the support substrate (or support) and the support substrate (or support) that was maintained until just before the peeling process.

[0077] (D) As a UV absorber, one or more types selected from benzotriazole compounds and hydroxyphenyltriazine compounds are preferred in terms of the degree of overlap with the UV laser wavelength in the UV absorption wavelength range, UV absorption characteristics at the same wavelength, low outgassing, and heat resistance.

[0078] As benzotriazole compounds, one or more selected from the group consisting of 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2,2'-methylenebis[6-(2H-benzotriazole-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole are particularly preferred in terms of compatibility with resin components, UV absorption characteristics, low outgassing, and heat resistance.

[0079] As hydroxyphenyltriazine compounds, one or more selected from the group consisting of 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris-(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine are particularly preferred in terms of compatibility with component (A), UV absorption characteristics, low outgassing, and heat resistance.

[0080] In a preferred embodiment for a UV laser peeling process, the most preferred UV absorber is one or more selected from the group consisting of 2,4,6-tris-(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, or 2,2'-methylenebis[6-(2H-benzotriazole-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol]. These have excellent compatibility with component (A), high melting points, and relatively low vapor pressure under temperature conditions of about 300°C or lower, so they can be selected within a wide range of usage and can also contribute to reducing outgassing from the composition for temporary fixation after curing under these temperature conditions.

[0081] (D) Most preferably, an absorbent selected from the UV transmittances mentioned below may be used as the UV absorber. By having such UV transmittances, the effect of appropriately controlling the curing and peeling of the composition can be obtained.

[0082] For a solvent that has no maximum absorption at wavelengths of 290 to 410 nm, when a UV absorber is dissolved at a concentration of 0.002 mass%, it is preferable that the transmittance at a wavelength of 355 nm at an optical path length of 1 cm is 50% or less, and also that the transmittance at a wavelength of 385 to 420 nm is higher than 50%. More preferably, the transmittance at a wavelength of 355 nm is 40% or less, and the transmittance at a wavelength of 385 to 420 nm may be 60% or more.

[0083] The most desirable (D) UV absorbers include the following.

[0084] 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (BASF Tinuvin 900, Adecastab LA-24, Everlight Chemical EVERSORB 76 / EVERSORB 234, molecular weight 447), which has a transmittance of 20% or less at a wavelength of 355 nm and a transmittance of 60% or more at a wavelength of 385 to 420 nm when dissolved at a concentration of 0.002 mass% in toluene used as a solvent.

[0085] 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (BASF Tinuvin 928, Everlight Chemical EVERSORB 89 / 89FD, molecular weight 442), which has a transmittance of 30% or less at a wavelength of 355 nm and a transmittance of 70% or more at a wavelength of 385 to 420 nm when dissolved in toluene as a solvent at a concentration of 0.002 mass%.

[0086] 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (BASF Tinuvin 405, molecular weight 584), which has a transmittance of 40% or less at a wavelength of 355 nm and a transmittance of 90% or more at a wavelength of 385 to 420 nm when dissolved in tetrahydrofuran as a solvent at a concentration of 0.002 mass%.

[0087] 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine (BASF Tinuvin 460, molecular weight 630), dissolved in tetrahydrofuran as a solvent at a concentration of 0.002 mass%, having a transmittance of 10% or less at a wavelength of 355 nm with an optical path length of 1 cm, and a transmittance of 80% or more at a wavelength of 385 to 420 nm.

[0088] The UV transmittance of the cured body in this specification is a value that can be obtained by reflectance measurement spectroscopy. Specifically, the transmittance can be obtained by using a reflectance spectroscopy measuring device (V-650 manufactured by Nippon Spectroscopic Scheme Co., Ltd.) using a cured body film with a thickness of about 50 μm, which is manufactured by sandwiching it onto a PET resin sheet under the following conditions.

[0089] Cell length: 10mM

[0090] Metering mode: T(Transmittance)

[0091] Measurement range: 450-200nm

[0092] Data storage interval: 1nm

[0093] UV / vis bandwidth: 2.0 nm

[0094] Response: medium

[0095] Scan rate: 40nm / min

[0096] Light source switching: 340nm

[0097] Light Source: D2 / WI

[0098] Filter Switch: Step

[0099] Correction: Baseline

[0100] The amount of the UV absorber (D) is preferably 0.01 to 5 parts by mass per 100 parts by mass of component (A), and more preferably 0.5 to 2.5 parts by mass. If the amount is 0.01 parts by mass or more, a sufficient UV laser peeling speed can be obtained, and if the amount is 5 parts by mass or less, the effect of low outgassing and heat resistance is less likely to be compromised can be obtained.

[0101] The present composition may include a monofunctional (meth)acrylate as component (E). As component (E), a monofunctional (meth)acrylate with a molecular weight of 550 or less is preferred, and a monofunctional alkyl (meth)acrylate having an alkyl group is more preferred.

[0102] As the alkyl group, it is preferable to have one or more selected from straight-chain alkyl groups, branched-chain alkyl groups, and alicyclic alkyl groups, and more preferable to have one or more selected from straight-chain alkyl groups and branched-chain alkyl groups. From the perspective of improving compatibility with component (A), it is preferable that component (E) has a long-chain, branched-chain, or cyclic alkyl group, and for example, has 18 to 40 carbon atoms, more preferably 18 to 32 carbon atoms, and has a branched-chain alkyl group such as an isostearyl group, an isotetracosanyl group (2-decyl-1-tetradecanyl group, etc.), an isotriacontanyl group (2-tetradecyl-1-octadecanyl group, etc.), or a cycloalkyl group. By using components with strong long-chain, high molecular weight, and aliphatic hydrocarbon characteristics (more preferably, enhancing the aliphatic hydrocarbon properties of the entire system), the low volatility, chemical resistance, and heat resistance required for the temporary fixation composition can be improved.

[0103] As component (E), one or more selected from the group consisting of stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, 2-dodecyl-1-hexadecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate are preferred. As component (E), the (meth)acrylate of Formula 1 below is preferred.

[0104] [Chemical Formula 1]

[0105]

[0106] R 1 It is a hydrogen atom or a methyl group, and a hydrogen atom is more preferred. R 2 is an alkyl group, and the number of carbon atoms is preferably 18 to 32. One or more of these (meth)acrylates may be used.

[0107] R 2As a monofunctional alkyl (meth)acrylate having an alkyl group having 18 to 32 carbon atoms, (meth)acrylates having straight-chain or branched-chain alkyl groups, such as stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicodecyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate, are preferred. From the perspective that it does not easily cause defects due to precipitation during manufacturing, R 2 It is preferable that the carbon number of is 18 or more and 23 or less.

[0108] In an embodiment containing component (E), the amount of component (E) used is preferably 50 parts by mass or less out of 100 parts by mass of the total of component (A) and component (E), more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less. In other embodiments, it is preferable that the composition does not contain component (E), and accordingly, it is possible to improve heat resistance by reducing the amount of outgassing. The amount of component (E) used may exceed 0% by mass.

[0109] The present composition may include a trifunctional (meth)acrylate as the (F) component. The molecular weight of the (F) component is preferably 900 or less, more preferably 700 or less, most preferably 500 or less, and even more preferably 400 or less.

[0110] Examples of trifunctional (meth)acrylates that may be included in (F) components include ethylene oxide modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, etc.

[0111] Examples of (meth)acrylates with four or more functional groups included in component (F) include ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxytetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Examples of (meth)acrylates with three or more functional groups included in component (F) include (meth)acrylate copolymers having (meth)acryloyl groups in their side chains.

[0112] (F) Among the components, a (meth)acrylic copolymer having (meth)acryloyl groups in the side chain is preferred. Examples of (meth)acrylic copolymers having (meth)acryloyl groups in the side chain include "ART CURE RA-341" manufactured by Negami Industrial Co., Ltd.

[0113] The amount of component (F) used is preferably 50 parts by mass or less out of 100 parts by mass of the total of component (A) and component (F), more preferably 1 to 40 parts by mass, and even more preferably 20 to 30 parts by mass. If the amount of component (F) is 50 parts by mass or less, the composition after mixing is less likely to undergo phase separation, and the effect of not significantly reducing heat resistance can be obtained. The amount of component (F) used may exceed 0% by mass.

[0114] The weight-average molecular weight in this specification is a value equivalent to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight-average molecular weight can be obtained by using a GPC system (SC-8010 manufactured by Tosho Co., Ltd.) with tetrahydrofuran as a solvent under the following conditions and by creating a calibration curve with commercially available standard polystyrene.

[0115] Flow rate: 1.0 ml / min

[0116] Set temperature: 40℃

[0117] Column composition: 1 unit of Tosho Co., Ltd. "TSK guardcolumn MP(ХL)" 6.0mm ID × 4.0cm, and 2 units of Tosho Co., Ltd. "TSK-GELMULTIPOREHXL-M" 7.8mm ID × 30.0cm (theoretical number of layers: 16,000), total 3 units (total theoretical number of layers: 32,000)

[0118] Sample injection volume: 100μl (sample solution concentration 1mg / ml)

[0119] Fluid transfer pressure: 39 kg / cm² 2

[0120] Detector: RI detector (parallax refractive index detector)

[0121] In any embodiment of the present invention, a cured body of the composition described above may also be provided. Such curing may be carried out using a light source described below. When the cured body is formed into a cured film with a thickness of 50 μm, it is preferable to satisfy one or more of the following conditions, and more preferable to satisfy all of them. The following conditions may be satisfied, for example, by using a UV absorber.

[0122] ㆍAmong the light transmittance of the cured film, the light transmittance in the wavelength region of 395 nm or longer among the wavelengths of the light source used for curing shall be 70% or more.

[0123] ㆍAmong the light transmittance of the cured film, the light transmittance in the wavelength range of 385 nm or more and less than 395 nm among the wavelengths of the light source used for curing shall be 20% or more.

[0124] ㆍAmong the light transmittance of the cured film, the light transmittance at the wavelength (355nm) of the UV laser used for UV laser peeling shall be 1% or less.

[0125] By satisfying these conditions, it is possible to achieve a sufficiently high curing rate and a UV laser peeling rate for practical purposes. Furthermore, in addition to achieving a sufficiently high curing rate and a UV laser peeling rate, it is possible to reduce the rate of mass loss under heating conditions after curing (or reduce the amount of outgassing under high-temperature vacuum). A prefixing agent having these characteristics can be preferably used in processes including high-temperature vacuum processes such as ion implantation, annealing, or electrode formation by sputtering, particularly in the back-side process after thinning.

[0126] Spin coating is a method of applying a composition to the surface of a substrate by, for example, dropping a liquid composition onto the substrate and rotating the substrate at a predetermined rotational speed. High-quality coating films can be efficiently produced by spin coating.

[0127] The present composition may be used as a resin composition for temporary fixation, a temporary fixation adhesive, an adhesive sheet, or a temporary fixation adhesive for manufacturing electronic devices. In this specification, the temporary fixation composition, the temporary fixation resin composition, and the temporary fixation adhesive may be collectively referred to as a temporary fixation agent.

[0128] When bonding a substrate to be processed and an optically transparent support substrate (or support) using the present composition, the energy amount in visible light or ultraviolet light (wavelength or center wavelength 365 to 405 nm) is 1 to 20,000 mJ / cm² 2 It is desirable to investigate so that the energy amount becomes 1 mJ / cm². 2 Sufficient adhesion can be obtained at this level, and 20,000 mJ / cm² 2 If it is below this level, productivity is excellent, so decomposition products from the photoradical polymerization initiator do not form easily, and outgassing is suppressed. 1,000 ~ 10,000 mJ / cm² in terms of productivity, adhesion, low outgassing, and ease of peeling. 2 It is desirable that it is.

[0129] There are no particular limitations on the substrates adhered by the present composition, but at least one substrate is preferably a transparent substrate that transmits light. Examples of transparent substrates include inorganic substrates such as crystal, glass, quartz, calcium fluoride, and magnesium fluoride, and organic substrates such as plastic. Among these, inorganic substrates are preferred due to their versatility and the ability to achieve significant effects. Among the inorganic substrates, one or more selected from glass and quartz are preferred.

[0130] The present composition may be of the photocurable type, and the cured body provided thereby possesses excellent heat resistance and peelability. In one embodiment, the cured body of the composition of the present invention has a low outgassing amount even when exposed to high temperatures, making it suitable for bonding, encapsulating, and coating various optical components, optical devices, and electronic components. The composition of the present invention is suitable for applications requiring durability across various aspects, such as solvent resistance, heat resistance, and adhesion, particularly for semiconductor manufacturing processes.

[0131] The cured body of the present composition can be used in processes over a wide temperature range from room temperature to high temperature. The heating temperature during the process is preferably 350°C or lower, more preferably 300°C or lower, and most preferably 250°C or lower. In a preferred embodiment, the temperature at which the heating mass loss rate of the cured body becomes 2% may be 250°C or higher. Since the adhesive bonded by the present composition has high shear adhesion, it can withstand thinning processes, etc., and can be easily peeled off after undergoing a heating process such as forming an insulating film. When used at high temperatures, the cured body of the present composition can be used in high-temperature processes, for example, preferably at 200°C or higher, more preferably at 250°C or higher.

[0132] In one embodiment, an adhesive is also provided in which a substrate is bonded by using the present composition as an adhesive. The adhesive can be peeled off by applying an external force. For example, it can be peeled off by inserting a cutting tool, a sheet, or a wire into the bonded portion. Alternatively, it is also possible to peel it off by irradiating a UV laser or an IR laser across the entire surface from the optically transparent substrate side of the adhesive.

[0133] Method for manufacturing thin wafers

[0134] In one embodiment, a method for manufacturing a thin wafer may also be provided. The manufacturing method is characterized by using the above-described temporary fixing composition or temporary fixing adhesive (hereinafter, it may also be simply referred to as an adhesive or a temporary fixing agent) as an adhesive layer between a wafer having semiconductor circuits, etc. and a support. The manufacturing method of the thin wafer has the following processes (a) to (e).

[0135] [Process(a)]

[0136] Process (a) is a process of applying an adhesive by spin coating on a wafer having a circuit forming surface on one side and a non-circuit forming surface on the other side, and bonding the circuit forming surface of the wafer to a support with an adhesive in between, and bonding it to another support or wafer to which a circuit is attached under vacuum.

[0137] A wafer having a circuit-forming surface and a circuit-non-forming surface is a wafer in which one side is a circuit-forming surface and the other side is a circuit-non-forming surface. A wafer to which the present invention can be applied is typically a semiconductor wafer. Examples of such semiconductor wafers include not only silicon wafers but also gallium nitride wafers, lithium tantalate wafers, lithium niobate wafers, silicon carbide wafers, germanium wafers, gallium-arsenide wafers, gallium-phosphorus wafers, gallium-arsenide-aluminum wafers, etc. The thickness of the wafer is not particularly limited, but 600 to 800 μm is preferred, and 625 to 775 μm is more preferred. As a support, for example, a transparent substrate that transmits light is used.

[0138] [Process(b)]

[0139] Process (b) is a process of photocuring the adhesive. After the wafer processed body (laminated substrate) is formed, the energy amount in the visible light or ultraviolet region is 1 to 20,000 mJ / cm² (wavelength or center wavelength is preferably 350 to 405 nm, more preferably 365 to 405 nm, and most preferably 385 to 405 nm). 2 It is desirable to investigate so that the energy amount becomes 1 mJ / cm². 2 If it is above this level, sufficient adhesion can be obtained, and 20,000 mJ / cm 2 If it is below this level, productivity is excellent, making it difficult for decomposition products from photoradical polymerization initiators to form, and outgassing is also suppressed. 1,000 to 10,000 mJ / cm² in terms of productivity, adhesion, low outgassing, and ease of peeling. 2 It is more desirable.

[0140] When curing the composition, a black light, UV-LED, or visible light-LED may be used as a light source, and for example, a light source such as the following may be used. As a black light, a light containing a component with a wavelength of 385 nm or more is preferably used regardless of its center wavelength. In addition, when a range of wavelengths is described in this specification, whether it falls within that range is determined based on whether the center wavelength is included in that range.

[0141] · Black light (center wavelength 365nm, illuminance 10mW / cm²) 2 , Toyo Adtech Co., Ltd. TUV-8271)

[0142] · UV-LED (Wavelength 385±5nm, Illuminance 350mW / cm²) 2 (Condition: Work distance from the end of the mirror unit 20mm), Mirror unit designed exclusively for HOYA Corporation H-4MLH200-V2-1S19+)

[0143] · UV-LED (Wavelength 395±5nm, Illuminance 375mW / cm² 2 (Condition: Work distance from the end of the mirror unit 20mm), Mirror unit designed exclusively for HOYA Corporation H-4MLH200-V3-1S19+)

[0144] · UV-LED (Wavelength 405±5nm, Illuminance 400mW / cm²) 2 (Condition: Work distance from the end of the mirror unit 20mm), Mirror unit designed exclusively for HOYA Corporation H-4MLH200-V4-1S19+)

[0145] · UV-LED (Center wavelength 405nm, Illuminance 10mW / cm²) 2 , CCS HLDL-120V0-NWPSC)

[0146] · Visible Light LED (Wavelength 451±5nm, Illuminance 550mW / cm² 2 (Condition: Work distance from the tip of the inspection unit 10mm), CCS Co., Ltd. HLDL-155VL450-PSC)

[0147] · Visible Light LED (Wavelength 492±5nm, Illuminance 400mW / cm²) 2 (Condition: Work distance from the tip of the inspection unit 10mm), HLDL-155BG-PSC manufactured by CCS Co., Ltd.)

[0148] In a preferred embodiment, a UV-LED or visible light-LED may be used as a light source, which has a lower integrated light amount (allowing for a shorter irradiation time) than a black light, which tends to have a high integrated light amount and a long irradiation time because the irradiation wavelength is generally broad. That is, by using an LED light source with a narrow irradiation wavelength band, temporary fixation can be performed in a short time, thereby achieving the effect of reducing the time required for the manufacturing process.

[0149] [Process(c)]

[0150] Process (c) is a process of grinding and / or polishing the non-circuit forming surface of a wafer bonded to a support, that is, a process of grinding the back side of the wafer of the wafer processed body obtained by bonding in process (a) to reduce the thickness of the said wafer. The thickness of the thinned wafer is preferably 10 to 300 μm, and more preferably 30 to 100 μm. There are no particular restrictions on the method of grinding / polishing the back side of the wafer, and known grinding / polishing methods are employed. It is preferable to perform grinding while cooling by pouring water over the wafer and the grinding wheel (such as a grinding wheel with a diamond blade attached).

[0151] [Process(d)]

[0152] Process (d) is a process of processing the non-circuit forming surface of a wafer processed body that has been ground / polished, i.e., a wafer processed body thinned by back-side grinding / polishing. This process includes various processes used at the wafer level. Examples include electrode formation, metal wiring formation, and protective film formation. More specifically, examples include conventional known processes such as metal sputtering for forming electrodes, wet etching for etching the metal sputtering layer, application of a resist to form a mask with metal wiring, formation of a pattern by exposure and development, peeling of the resist, dry etching, formation of metal plating, silicon etching for forming TSVs, and formation of an oxide film on the silicon surface.

[0153] [Fair(e)]

[0154] Process (e) is a peeling process. This process is a process of peeling the wafer processed in process (d) from the wafer body. For example, after performing various processing on the thinned wafer, it is a process of peeling the wafer from the wafer body before dicing. At this time, a dicing tape may be attached to the surface that has been thinned and processed in advance. This peeling process is generally carried out under relatively low temperature conditions ranging from room temperature to about 60°C. As this peeling process, known UV laser peeling processes, IR laser peeling processes, or mechanical peeling processes may all be employed.

[0155] A UV laser peeling process is a process in which a UV laser is irradiated onto the entire surface of a wafer workpiece, for example, by scanning it in a straight line in a tangential direction from the optically transparent support side end of the wafer workpiece, and the adhesive layer is decomposed and peeled off by the energy of the laser. Such a peeling process is described, for example, in Japanese Patent Publication No. 2019-501790 or Japanese Patent Publication No. 2016-500918.

[0156] The IR laser peeling process is a process in which an IR laser is irradiated onto the entire surface of a wafer workpiece, for example, by scanning it in a straight line in a tangential direction from the optically transparent support side end of the wafer workpiece, and the adhesive layer is heated and decomposed by the laser energy to peel it off. Such a peeling process is described, for example, in Patent Publication No. 4565804. To perform this IR laser peeling process, a photothermal conversion layer that absorbs IR laser light and converts it into heat (for example, 3M’s LTHC; Light-To-Heat-Conversion release coating) may be installed between the temporary fixing agent layer and the glass support. When using 3M’s LTHC, for example, the LTHC is spin-coated onto the glass support and cured. Then, the temporary fixing agent layer can be spin-coated onto the wafer and then UV-cured by attaching it to the glass support on which the LTHC layer is formed. A method for performing an IR laser peeling process using 3M’s LTHC is described, for example, in Patent Publication No. 4565804, which is identical to the above.

[0157] A mechanical peeling process is a peeling process that includes, for example, inserting a blade into the interface end of a wafer workpiece to cause a split between the wafer and the support, fixing the wafer of the wafer workpiece horizontally with the wafer facing downward, and after inserting the blade, applying upward stress to the upper support and / or the blade to advance the split and peel the wafer and the support. Such a peeling process is described, for example, in Japanese Patent Publication No. 6377956 or Japanese Patent Publication No. 2016-106404.

[0158] When peeling off the present composition, any one of these peeling methods may be used. At this time, it is preferable to fix one side of the wafer or support of the wafer workpiece horizontally and insert a blade, or to swell the outer periphery of the adhesive layer with a solvent (e.g., aliphatic or aromatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, mesitylene, etc.) to create a peeling initiation, and then lift the other side at a certain angle from the horizontal direction. This peeling method is typically carried out at room temperature, but it is also preferable to heat it to an upper limit of about 90°C. When using a laser, it is preferable to use a YAG laser or a YVO4 laser.

[0159] The process of peeling the wafer processed in the above process (e) from the support is additionally, in the case of a mechanical peeling process

[0160] (f) A process of attaching a dicing tape to the wafer surface of a processed wafer, and

[0161] (g) A process of vacuum adsorbing the dicing tape surface onto the adsorption surface, and,

[0162] (h) A process of peeling off the support from the wafer processed at a temperature range of 10 to 100℃ on the adsorption surface.

[0163] It is desirable to include [this]. By doing so, the support can be easily peeled off from the wafer that has been processed, making it easier to perform the dicing process later.

[0164] In addition, in cases where exfoliation is performed using a UV laser or IR laser, the corresponding manufacturing method additionally, for example,

[0165] (i) A process of installing / fixing a processed wafer in a horizontal location, preferably via a dicing tape, with the optically transparent support side facing upward, and

[0166] (j) A process of irradiating the front surface of the wafer by scanning a laser from the support side of the wafer that has undergone processing.

[0167] It is desirable to include [this]. By doing so, the support can be easily peeled off from the processed wafer, making it easier to perform the dicing process later.

[0168] In addition, after the process of peeling the wafer processed in process (e) from the support using a UV laser or IR laser,

[0169] (k) Process for removing residual fixative remaining on the wafer surface

[0170] It is necessary to perform the following. Methods for removing the temporary fixative include a method in which an adhesive tape, such as dicing tape, is attached to the entire surface of the other side where the temporary fixative remains while the thinned side is vacuum-adsorbed to the adsorption surface, and the temporary fixative is peeled off from each tape; and a method in which the wafer is immersed in a solvent (e.g., aliphatic or aromatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, and mesitylene) to swell and peel off the adhesive layer. Among these methods, the tape peeling method is preferred because it involves fewer process steps and a shorter required time.

[0171] After the removal of the temporary fixative, the wafer may proceed to the next process as is without surface cleaning. If cleaning is performed, additionally

[0172] (l) A process of cleaning a wafer from which the support and prefixing agent have been removed using a solvent (e.g., an aliphatic or aromatic hydrocarbon solvent such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, mesitylene, etc.) with the circuit forming surface facing upward.

[0173] It is desirable to carry out...

[0174] In some cases, adhesive (fixing agent) may remain on the circuit forming surface of the wafer from which the fixing agent has been removed by process (k). Additionally, while it is desirable to clean and reuse the peeled support, adhesive residue may also be adhered to the surface of the support. Methods for removing such adhesive residue include immersing the support in a solvent (e.g., aliphatic or aromatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, decane, benzene, toluene, xylene, and mesitylene) and peeling it off by swelling.

[0175] In one embodiment, when curing the above composition to obtain a cured body, various methods as follows may be employed.

[0176] First, as a first method, a single-layer hardened body can be obtained by hardening a layer made of a temporary fixation composition containing the above-described components.

[0177] Furthermore, as a second method, a method may be used to obtain a cured body having an integrated single layer or multiple layers by preparing and curing a first layer composed of a temporary fixation composition containing at least component (A) and component (B) but not including the UV absorber component (D), and a second layer composed of a temporary fixation composition containing at least components (A), (B), and (D). In this cured body, it is preferable that the concentration distribution of the components differs with respect to the thickness direction, or that the concentration distribution of the components differs between the upper and lower surfaces with respect to the thickness direction of the cured body. The difference in the concentration distribution of the components can be confirmed by quantifying the UV transmittance on both sides of the cured body using the reflectance measurement spectroscopic method described above. By combining layers with different light transmittances using this method, the effect of achieving optimal curing can be obtained. Additionally, a black light or a UV-LED can be used as a light source during the curing described above (the same applies to the following method). An example of a black light is the TUV-8271 manufactured by Toyo Adtec Co., Ltd. (center wavelength 365 nm, illuminance 10 mW / cm²) 2Examples include the HOYA Corporation H-4MLH200-V2-1S19+ dedicated mirror unit (wavelength 385±5nm, illuminance 350mW / cm²) as a UV-LED. 2 , Condition: Scan pitch 20mm from the end of the mirror unit), Mirror unit designed exclusively for HOYA Corporation H-4MLH200-V3-1S19+ (Wavelength 395±5nm, Illuminance 375mW / cm²) 2 , Condition: Work distance from the end of the mirror unit 20mm), Mirror unit designed exclusively for HOYA Corporation H-4MLH200-V4-1S19+ (Wavelength 405±5nm, Illuminance 400mW / cm²) 2 Examples include: , condition: work distance from the end of the mirror unit 20mm).

[0178] In addition, as a third method, it is also possible to obtain a cured body having at least a partially integrated single layer by applying component (D) onto a cured layer composed of a temporary fixation composition containing at least component (A) and component (B) (e.g., by spin coating). In this case, the concentration distribution of the components differs with respect to the thickness direction of the cured body. As described above, the concentration distribution of the components can be quantified by reflectance measurement spectroscopy for each target layer. Through this method, the effect of being able to precisely control UV absorption characteristics can be obtained.

[0179] In addition, as a fourth method, a multilayer cured body may be obtained by placing a layer of a commercially available LTHC agent (photothermal converter) on a layer of a pre-fixing composition comprising at least component (A) and component (B) and curing it. This allows for the effect of easily obtaining a cured body.

[0180] The cured body obtained by the above-described method can be combined with a substrate to provide a structure.

[0181] Various examples may be given for the method of manufacturing the structure described above. For example, the first manufacturing method may include the step of applying a first provisional fixing composition containing at least component (A) and component (B) and not component (D) onto a wafer and partially curing it, the step of applying a second provisional fixing composition containing at least components (A), (B), and (D) onto the partially cured provisional fixing composition, and the step of placing a transparent substrate onto the applied second provisional fixing composition and photocuring it.

[0182] Additionally, as a second method for manufacturing a structure, the method may include the step of applying a first provisional fixing composition containing at least component (A) and component (B) and not component (D) onto a wafer and partially curing it as needed, the step of applying a second provisional fixing composition containing at least components (A), (B), and (D) onto a transparent substrate and partially curing it as needed, and the step of bringing the surfaces of the wafer and the transparent substrate, each having the provisional fixing composition applied to them, into close contact and then bonding them by photocuring.

[0183] In addition, as a third method for manufacturing a structure, the method may include the step of applying a temporary fixing composition containing at least component (A) and component (B) and not component (D) onto a wafer and partially curing it as needed, the step of applying an LTHC layer onto a transparent substrate and drying and curing it, and the step of bonding the side of the wafer where the temporary fixing composition is applied and the side of the transparent substrate where the LTHC layer is applied by photocuring.

[0184] Apart from the above-mentioned temporary fixation composition, the same composition used in the temporary fixation composition of the present invention can also be used as a raw material for a photothermal conversion (LTHC) layer that absorbs IR laser light and converts it into heat, as described in Patent Publication No. 4565804. By adding this composition as a component of the photothermal conversion (LTHC) layer, its heat resistance can be improved.

[0185] In one embodiment, a method for manufacturing a semiconductor wafer may be provided, comprising the steps of: applying a temporary fixing composition to a semiconductor wafer substrate and / or a support member to bond the semiconductor wafer substrate and the support member; curing the temporary fixing adhesive by irradiating it with light of a wavelength of 350 to 700 nm (preferably 365 to 500 nm, more preferably 385 to 450 nm) to obtain an adhesive; and irradiating the adhesive with laser light of a wavelength of less than 385 nm (preferably laser light of a wavelength of 200 nm or more and less than 385 nm) to peel off the semiconductor wafer substrate. The present manufacturing method has the advantage that the curing and peeling steps are both processes performed at room temperature, there is no need to heat or cool the member, and generally there is no need to use a solvent, making it simple and having a short cycle time.

[0186] Furthermore, the cured temporary fixing adhesive may form a single layer within the adhesive. By doing so, it is possible to simplify the process or shorten the takt time.

[0187] In a preferred embodiment, by including both the photoradical polymerization initiator of component (B) and the UV absorber of component (D) described above, it is possible to achieve both a fast curing speed and a fast peeling speed, even with a single-layer temporary fixing adhesive. Furthermore, when the temporary fixing adhesive is UV-cured, the uncured UV-curable monomer components remaining in the cured body can be significantly reduced, thereby improving the heat resistance of the cured body and reducing volatile matter under a nitrogen atmosphere. That is, for example, it becomes possible to increase the 2% heat loss temperature when measuring the Tg / DTA of the cured body. A temporary fixing adhesive with high heat resistance and reduced volatile matter under a nitrogen atmosphere is extremely useful in recent semiconductor manufacturing processes. The cured body preferably has a 2% mass loss temperature under a nitrogen atmosphere of 300°C or higher, preferably 320°C or higher, and more preferably 326°C or higher.

[0188] Examples

[0189] The present invention will be described in more detail below based on examples and comparative examples, but the invention is not limited thereto.

[0190] Unless otherwise noted, experiments were conducted at 23°C and 50% humidity. Curable resin compositions (hereinafter referred to as liquid resin compositions) with the compositions shown in the table below (units are parts by mass) were prepared and evaluated. The following compounds were selected as each component.

[0191] [Table 1]

[0192]

[0193] [Table 2]

[0194]

[0195] [Table 3]

[0196]

[0197] (furtherance)

[0198] (A-1) The following was used as a component.

[0199] A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate (Shinnakamura Chemical Co., Ltd. "NK ester A-BPEF-2")

[0200] A-BPE-2: Ethoxylated bisphenol A diacrylate ("NK Ester A-BPE-2" manufactured by Shinnakamura Chemical Industry, R=-CH2CH2O-, m=n=1 in the structural formula below)

[0201] A-BPP-3: Ethoxylated bisphenol A diacrylate ("NK Ester A-BPP-3" manufactured by Shinnakamura Chemical Industry, R=-CH2CH(CH3)-, m+n≈3 in the structural formula below)

[0202] ABE-300: Ethoxylated bisphenol A diacrylate ("NK ester ABE-300" manufactured by Shinnakamura Chemical Industry, R=-CH2CH2O-, m+n≈3 in the structural formula below)

[0203] [Chemical Formula 2]

[0204]

[0205] (A-2) The following was used as a component.

[0206] HBPE-4: EO-modified hydrogenated bisphenol A diacrylate (Daiichi Pharmaceutical Co., Ltd. "HBPE-4", m+n≈4)

[0207] A-DCP: Tricyclodecanedimethanol diacrylate (Shinnakamura Chemical Co., Ltd. "NK Ester A-DCP")

[0208] (B) The following was used as a component.

[0209] Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Irgacure 819")

[0210] (C) The following was used as a component.

[0211] HX-620: Caprolactone-modified hydroxypivaline neopentyl glycol diacrylate (Japan Chemical Co., Ltd. "Kayarad HX-620", m+n≒4)

[0212] HX-220: Caprolactone-modified hydroxypivaline neopentyl glycol diacrylate (Japan Chemical Co., Ltd. "Kayarad HX-220", m+n≒2)

[0213] PHOTOMER-4362: Hexanediol[2PO]diacrylate (IGM "PHOTOMER 4362")

[0214] DDDA: 1,10-Decanediold Diacrylate (Hitachi Chemical "FA-1210A")

[0215] NDDA: 1,9-Nonanediol diacrylate (Osaka Organic Chemical Industry Co., Ltd. "Viscot #260")

[0216] RC100C: Acrylate polymer having acryloyl groups at both ends (Kaneka Corporation's "Kaneka XMAP RC100C", having the following structural formula)

[0217] [Chemical Formula 3]

[0218]

[0219] (D) The following was used as a component.

[0220] 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine (BASF "Tinuvin 460")

[0221] (E) The following was used as a component.

[0222] DTDA: 2-decyl-1-tetradecanyl acrylate (Kyoei Chemical Co., Ltd. "Light Acrylate DTD-A")

[0223] nSTA: n-isosteallyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd. "STA")

[0224] ISTA: Isostearyl acrylate (Osaka Organic Chemical Industry Co., Ltd. "ISTA")

[0225] (F) The following was used as a component.

[0226] RA-341: Polyfunctional methacrylate polymer with three or more functions ("ART CURE RA-341" manufactured by Negami Industry, weight average molecular weight approx. 80,000)

[0227] (Liquid sample production)

[0228] The materials were heated and mixed at 80°C to form a homogeneous mixture. In addition, examples in which precipitation occurred at this stage were excluded from subsequent evaluations. Furthermore, as described below, cases in which hardening failure occurred when hardened, and cases in which melted at 300°C or lower during heating were also excluded from evaluations.

[0229] (Measurement of storage modulus)

[0230] The liquid resin composition homogenized by the above heated mixing is embedded in a PET film and expanded until it reaches a thickness of 50 μm, resulting in an integrated light intensity of 5000 mJ / cm² 2 Cured specimen samples were prepared by curing under the following conditions. For curing, a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²) was used. 2 , CCS HLDL-120V0-NWPSC) was used.

[0231] The dynamic viscoelasticity of the hardened sample was measured using the RSA-G2 viscoelasticity measuring device manufactured by TA Instruments Japan. The measurement was performed with a chuck distance of 7 mm, a sample width of 5 mm, a sample thickness of 50 μm, a distortion of 0.1%, a tensile frequency of 1 Hz, a heating rate of 3 ℃ / min, and a temperature range of -50 ℃ to 250 ℃, and the value of E' at 23 ℃ was obtained.

[0232] (Measurement of 2% mass loss temperature)

[0233] The liquid resin composition homogenized by the above heated mixing is embedded in a PET film and expanded until it reaches a thickness of 50 μm, resulting in an integrated light intensity of 5000 mJ / cm² 2Cured specimen samples were prepared by curing under the following conditions. For curing, a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²) was used. 2 , CCS HLDL-120V0-NWPSC) was used.

[0234] 10 mg of a weighed hardened sample was heated from room temperature to 600°C at a heating rate of 10°C / min under a nitrogen gas stream with a carrier gas flow rate of 70 ml / min using a differential heat and thermal mass simultaneous measuring device "STA-2500" manufactured by Nechi Japan, and then the hardened sample was weighed. By doing so, the heating mass loss rate (2% mass loss temperature) under a nitrogen atmosphere was calculated.

[0235] (Evaluation of vacuum heat resistance)

[0236] A 4-inch sample was prepared by bonding a 4-inch silicon wafer (diameter 10 cm × thickness 50 μmt) and a 4-inch glass wafer (diameter 10 cm × thickness 0.7 mm) using the prepared liquid resin composition. Similarly, an 8-inch sample was prepared by bonding an 8-inch silicon wafer (diameter 10 cm × thickness 50 μmt) and an 8-inch glass wafer (diameter 20 cm × thickness 70 μmt) using the same liquid resin composition. During bonding, the thickness of the resin composition was adjusted by using a mixture prepared by adding 0.1 mass% of silica particles manufactured by Ube Eximosa (product name Hyfreshka TS N3N, average particle size 50 μm) to the temporary fixative. After bonding, the LED integrated luminous intensity was 5000 mJ / cm² 2 (Center wavelength 405nm, illuminance 100mW / cm² 2 Bonded samples were fabricated by curing under the conditions of ). For curing, UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²) 2 , CCS HLDL-120V0-NWPSC) was used.

[0237] Each bonded sample was placed in a vacuum hot plate chamber and heated for 1 hour under conditions of 300°C and 20 Pa, after which the circumferential end of the bonded sample was visually inspected and evaluated according to the following criteria. The evaluation result of the 4-inch sample is indicated as "Vacuum heat resistance 4 in 50 μmt" in the table. The evaluation result of the 8-inch sample is indicated as "Vacuum heat resistance 8 in 70 μmt" in the table.

[0238] Excellent: The end part did not peel off at all.

[0239] Good: The length of the peeling spot at the end was less than 5 mm from the edge.

[0240] Possible: The length of the peeling spot at the end was 5mm or more and less than 10mm from the edge.

[0241] Impossible: The length of the peeling spot at the end was 10 mm or more from the edge.

[0242] (Evaluation of tape peelability)

[0243] A release tape (Denka "ELEGRIP (registered trademark) TAPE P-Series") attached to the above bonded sample was used as a peel sample. A peel test was performed under the following conditions using a 2-axis tensile test system (Shimadzu "Autograph AG-Xplus").

[0244] Detachment direction: 90°

[0245] Peeling speed: 2mm / sec

[0246] Measurement width: 25mm

[0247] Stroke: 80mm

[0248] Test thickness: 0.070mm

[0249] Push rod: φ7mm

[0250] Pressure: 1N / mm 2

[0251] Visually checked whether the tape had split during peeling.

[0252] From the above results, the compositions according to the embodiments of the present invention exhibited excellent heat resistance and tape peelability. On the other hand, Comparative Examples 1 to 4, 7, 8, and 12 to 16, which did not satisfy the storage modulus condition, all had difficulty with tape peelability. In addition, Comparative Examples 9 to 11, which did not contain component (A), all showed poor prognosis. Comparative Example 5, which had a storage modulus exceeding 0.66 GPa, had difficulty with heat resistance. Comparative Example 6 also did not satisfy the conditions of the present invention because it had no substantial storage modulus due to precipitation during manufacturing.

[0253] An experiment was conducted to grind the non-circuit forming surface (back side) of a silicon wafer processed body obtained by bonding a silicon wafer to a glass support using the compositions of Examples 3 and 4 (i.e., reproduction of the above process (c)). Before processing, the thickness of the glass support was approximately 715 μm and the thickness of the silicon wafer was approximately 722 μm. The thickness was calculated as the average of the results of 5 trials.

[0254] Thickness of a silicon wafer processed body using the composition of Example 3 as a temporary fixing adhesive layer

[0255] Before backhand grinding: 1506.6μm

[0256] After backside grinding: 833.8μm

[0257] Thickness of silicon wafer after grinding: 49.7μm

[0258] Thickness of a silicon wafer processed body using the composition of Example 4 as a temporary fixing adhesive layer

[0259] Before backhand grinding: 1508.8μm

[0260] After backside grinding: 835.0μm

[0261] Silicon wafer thickness after grinding: 49.8μm

[0262] From the above experimental results, it was confirmed that the silicon wafer can be preferably thinned in a silicon wafer processed body using the composition according to the embodiment of the present invention as a temporary fixing adhesive.

Claims

Claim 1 A temporary fixation composition characterized by containing (A-1) and (A-2) and (B) as the following (A) components, wherein the storage modulus of the cured body at 23°C is 0.01 GPa or more and 0.66 GPa or less: (A-1) an aromatic difunctional (meth)acrylate having a condensed ring backbone, (A-2) an alicyclic difunctional (meth)acrylate, and (B) a photoradical polymerization initiator; wherein the cured body is formed by embedding the temporary fixation composition into a PET film, expanding it until it reaches a thickness of 50 μm, and applying a UV-LED (center wavelength 405 nm, illuminance 100 mW / cm²). 2 Using ) accumulated luminous energy 5000mJ / cm 2 It hardened under the conditions of. Claim 2 A composition for temporary fixation according to claim 1, characterized in that (A) the component comprises (A-1) an aromatic difunctional (meth)acrylate having a condensed ring backbone, and (A-2) an alicyclic difunctional (meth)acrylate having a condensed ring backbone. Claim 3 A composition for temporary fixation according to claim 1 or claim 2, further comprising the following (C): (C) acyclic aliphatic difunctional (meth)acrylate. Claim 4 A composition for temporary fixation according to claim 3, wherein (C) the component comprises an oligomer and / or polymer. Claim 5 A composition for temporary fixation according to claim 3, wherein the amount of component (A) is 50% or more in a mass ratio in which the sum of component (A) and component (C) is 100 mass%. Claim 6 A composition for temporary fixation according to claim 1 or claim 2, further comprising the following (D): (D) a UV absorber. Claim 7 A composition for temporary fixation according to claim 1 or claim 2, further comprising the following (E): (E) monofunctional (meth)acrylate. Claim 8 A composition for temporary fixation according to claim 7, containing more than 0% and less than or equal to 50% of component (E) in a mass ratio where the sum of component (A) and component (E) is 100 mass%. Claim 9 A composition for temporary fixation according to claim 1 or claim 2, which does not contain monofunctional (meth)acrylate. Claim 10 A composition for temporary fixation according to claim 1 or claim 2, further comprising the following (F): (F) a polyfunctional (meth)acrylate with three or more functionalities. Claim 11 A composition for temporary fixation according to claim 10, wherein the mass ratio of component (F) is greater than 0% and less than or equal to 50%, wherein the sum of component (A) and component (F) is 100 mass%. Claim 12 A cured body of the temporary fixation composition described in claim 1 or claim 2. Claim 13 A cured body according to claim 12, wherein the 2% mass loss temperature measured after heating from room temperature to 600°C at a heating rate of 10°C / min under a nitrogen atmosphere with a nitrogen air stream of 70 ml / min is 300°C or higher.

Citation Information

Patent Citations

  • Photocurable composition

    WO2015056632A1

  • Photoradically polymerizable composition

    WO2021172341A1

  • Curable resin composition for optical recording medium, cured product and optical recording medium

    JP2011173981A

  • (METH) acrylic resin composition and adhesion / dismantlement method

    JP2014091774A

  • Composition

    WO2021235406A1